Consommation de tabac : Facteur de risque pour la consommation de drogues - GUEMAZ, Farida; DJENIDI, Fayza (Journal of Human Sciences, 2015)
This article aims to highlight the role of smoking as a risk factor for the use of drug among adolescents. Since the latter increasingly being perceived by adolescents as  frustrating social codes transgression, there is the desire in it to play with risk, while sucking also to reach through this act to a state of wholeness and self-assertion, from there, his identity  is built, his personality is confirmed; a personality rather suspicious towards adults.The objective of this research is to analyze and discuss adolescence as a period of risk which involves adolescents in several behavioral problems including smoking and drugs taking which are the most important. From this synthesis the researcher has emphasized on the process of addiction and tobacco use as one of the factors of illegal drugs consumption.In this article we have mentioned the most important challenges encountered by the United Nations, and nongovernmental organizations in facing the phenomenon of smoking which is not only a public health problem and all associated ones, but a risk factor for the involvement of adolescents in more complicated problems such as addiction to illicit drugs.